2003
DOI: 10.1046/j.1523-1755.2003.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

High glucose levels inhibit focal adhesion kinase-mediated wound healing of rat peritoneal mesothelial cells

Abstract: Our results demonstrate that high glucose concentrations as well as high osmolarity inhibit FAK-mediated migration of mesothelial cells, and suggest that dialysates containing high glucose concentrations may cause peritoneal damage by inhibiting wound healing of the mesothelial cell monolayer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 36 publications
6
37
0
5
Order By: Relevance
“…In line with our observations, previous studies showed that high concentrations of glucose and GDPs suppress MC wound healing. High glucose inhibits integrin-mediated cell migration along the basal membrane (36), and GDPs decrease the velocity of MC wound closure and impair MC viability in vitro (37). Furthermore, compared with MCs taken from glucose effluents, those taken from icodextrin effluents show greater proliferation ex vivo (38).…”
Section: Discussionmentioning
confidence: 99%
“…In line with our observations, previous studies showed that high concentrations of glucose and GDPs suppress MC wound healing. High glucose inhibits integrin-mediated cell migration along the basal membrane (36), and GDPs decrease the velocity of MC wound closure and impair MC viability in vitro (37). Furthermore, compared with MCs taken from glucose effluents, those taken from icodextrin effluents show greater proliferation ex vivo (38).…”
Section: Discussionmentioning
confidence: 99%
“…They distribute widely on the surface of omentum and peritoneum and are easy to harvest with a small umbilical incision. They are also easy to be cultured in vitro and the commonly used DMEM medium could satisfy their nutritional requirement [10,11]. Mesothelium-lined grafts including peritoneum [12,13] and tunica vaginalis [14,15] have already been attempted in urethral reconstruction with good results.…”
Section: Discussionmentioning
confidence: 99%
“…FAK plays a critical role in cell survival and is phosphorylated when cells are treated by mannitol [14,21,42].…”
Section: Discussionmentioning
confidence: 99%
“…Among the cytoskeletal-associated proteins, FAK has been proposed to be a critical factor in modulating cytoskeletal changes [7,43]. Due to the fact that FAK activation is also known to be linked with PKC activity [8,15,17,42], FAK is likely to play a fundamental role in mesangial cell contraction.…”
Section: Introductionmentioning
confidence: 99%